Exploring the impact of franchising on industry evolution : fast food / quick service restaurants (QSR) and real estate industries in Ireland - Beere, Rosalind (Trinity College (Dublin, Ireland). Trinity Business School, 2015)
The principal aim of this study was to explore and describe the role of franchising in terms of its emergence and impact on industry structure. The justification for the research was based on a number of theoretical and empirical grounds. These included the general neglect of the area in the literature, the potential implications for future research and potential contribution recognised by practitioners, policy makers, and academics.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin